A retained surgical drain in the abdomen for five years - Irpatgire, Ravindra Nagnath; Chakrod, Sharda Vithalreddy (International Surgery Journal, 2016)
Retained surgical drain in the peritoneal cavity is very rare but potentially dangerous error. Most cases are unreported because of the fear of medico-legal problems. Management of such iatrogenic complications requires repeated laparotomy or wound exploration. We reported a case of a large corrugated rubber drain migrated and retained accidently in the abdominal cavity in a patient who underwent exploratory laparotomy for peritonitis secondary to perforated appendix about five years ago.